Bio-based alkali-activated controlled low strength material: Engineering properties. (12th April 2021) - Ahadzadeh Ghanad, D.; Soliman, A.M.
Highlights: Bio-based alkali-activated CLSM is a sustainable method for reusing agriculture waste. Bio-based alkali-activated CLSM showed a compressive strength of 1.4–6.4 MPa at 28 days. Lightweight CLMs can be achieved through utilizing agriculture wastes as aggregate. Increasing agriculture waste content ≥40% is feasible to achieve excavatable CLSMs. Abstract: This study investigated the potential of unifying construction and agricultural sectors' goals to meet the global demand for green construction implementation. Saving natural resources and solving waste disposal of issues, through utilizing agriculture waste as a replacement for natural aggregate was adopted. Environmental-friendly controlled low strength materials (CLSMs) using alkali-activated binders as a replacement for regular cement was selected as a green application. Fresh, hardened and durability performance for mixtures with various agriculture waste contents (i.e. 0% up to 40% as replacement of fine natural aggregate) and binder activation levels were evaluated. Results reveal that increasing the agriculture waste content (i.e. >10%) increased the potential to achieve a lightweight green CLSM. All CLSM mixtures had exhibited strength below 8.3 MPa, satisfying the strength requirements for structural filling according to ACI committee 229. Only mixtures with agriculture waste contents >20% meet the desired strength for future re-excavation CLSMs (i.e. 2.1 MPa). Hence, low strength requirements for CLSMs had accommodated the strength reduction induced by agriculture waste addition. The findings pave the way for a wider implementation of agriculture wastes in green construction, providing economic and environmental benefits for both construction and agriculture sectors.